Role of Follicle Size, IGF-I, Glucose and Hormones on Nuclear Maturation Events of Awassi Sheep Oocytes (Ovis aries) - omar mardenli (ISPEC Journal of Agricultural Sciences)
This experiment aimed to study the combined effect of each of the follicle size, insulin-like growth factor (IGF-I), glucose and hormones (growth hormone (GH) and luteinizing hormone (LH)) on different phases of in vitro nuclear maturation of Awassi sheep oocytes. Follicles diameters were divided into two main groups: small follicles (SF): 1-2 mm and large follicles (LF): >2 mm. The levels (μg/ml) of Insulin-Like Growth Factor (IGF-I), GH, LH and glucose (mM) were determined according to two increasing shared concentrations (A:5,5,1 and 50; B:10,5.5,5 and 100 respectively). The maturation events were monitored at 7-time intervals (0,3,6,9,12,21 and 27 hours). Before incubation (0 - hour time interval), the oocytes in SF group outperformed their counterparts of LF group in the germinal vesicle phase (92.45% Vs 74.46%; p=0.01). Down to the 6- hour time interval, the oocytes in B solution achieved the highest rates (24.52%; LF group),  After 9 hours of incubation, the differences appeared clearly in the prometaphase -1(p=0.05) as half of the number of oocytes in B solution reached the stage (53.84%; LF group), the rates did not exceed 31.37% (A solution; SF group). In the 12 - hour time interval, the pro -metaphase-1 rates across the four groups reached the values :34.00% (A solution; SF group), 40.00% (B solution; LF group), 53.84% (A solution; SF group) and 58.49% (B solution; LF group) respectively. Upon 21- hour time interval, oocytes across the different groups showed a significant difference in metaphase-I (p=0.01) with the superiority of oocytes of B solution (33.96%; LF group). At the 24- hour time interval, the rates of oocytes involved in the metaphase-II were sub-intermediate and ranged between 20.00% and 36.00% without statistical significance. The final time interval (27- hours of incubation) showed a significant difference in the rates of the metaphase-II (p=0.002), as the oocytes of B solution showed a great superiority (84.61%; LF group). It is concluded from this study that the maturation of oocytes derived from large follicles (>2 mm) in a mixture of IGF-I, GH, LH (μg/ml) and glucose (mM) with the levels 10,5.5,5 and 100 respectively led to a significant increase in the rates of metaphase-II.